Principales microorganismos bacterianos causantes de mastitis bovina en fincas lecheras en el resguardo de Quizgo municipio de Silvia, Cauca (2024)
Since January 2023, milk samples were taken from some livestock families in the Quizgo reservation located in the municipality of Silvia Cauca, with the purpose of identifying bovine mastitis disease, whether subclinical or clinical, in each quarter (nipple) of the moving, through the use of a rapid field test called California Mastitis Test CMT which measures the concentration of somatic cells in each milk sample, with the aim of obtaining 150 samples positive for mastitis. In the second instance, the positive samples were taken to the laboratory of the Antonio Nariño University with the aim of subjecting them to different diagnostic tests in order to identify the type of bacteria that was causing the mastitis